Reliability Optimization Design of Rail-roader Electric Wheel Reducer - Yi Chengshan; Liu Yanhu; Cun Ligang; Sun Yunqi (Jixie chuandong)
From the perspective of the optimization design of rail-roader electric wheel,according to the working condition and load conditions of planetary gear,taking the volume,contact ratio,efficiency of NGW planetary gear transmission as the target function,optimization design of gear reducer is carried out based on the theory of reliability.The reliability of gear fatigue strength is combined within the constraint of optimization problem,the optimization parameters such as the minimum volume and quality of the machinery parts and components are obtained,the transmission efficiency remain before optimization level.By the optimization design of planetary gear reducer,the special requirements of rail-roader electric wheel are fulfilled.The reference forthe design of rail-roader provided.